2011
DOI: 10.1088/1742-5468/2011/09/p09026
|View full text |Cite
|
Sign up to set email alerts
|

Counting lattice animals in high dimensions

Abstract: Abstract. We present an implementation of Redelemeier's algorithm for the enumeration of lattice animals in high dimensional lattices. The implementation is lean and fast enough to allow us to extend the existing tables of animal counts, perimeter polynomials and series expansion coefficients in d-dimensional hypercubic lattices for 3 ≤ d ≤ 10. From the data we compute formulas for perimeter polynomials for lattice animals of size n ≤ 11 in arbitrary dimension d. When amended by combinatorial arguments, the ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…Recently, Luther and Mertens [8] provided an argument supporting this hypothesis. They showed that the highest-degree term in DX(n, n − k) is of the order 2 n n n+k−4 .…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Recently, Luther and Mertens [8] provided an argument supporting this hypothesis. They showed that the highest-degree term in DX(n, n − k) is of the order 2 n n n+k−4 .…”
Section: Resultsmentioning
confidence: 92%
“…where P k (n) is a monic polynomial in n. It has also been conjectured [2,8] that the degree of P k (n) is 3k − 4. One can attempt to prove this pattern for the general case of k without actually writing down all the expressions (respective of the cases in our method), but rather by showing that one of them (containing the dominant term, that is, having the highest degree of n) has the form 2 n n n−2k−1 (n − k) times a polynomial in n of degree 3k − 4, and that all the other expressions have the same form multiplied by polynomials of at most the same degree.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Aleksandrowicz and Barequet [3] provided counts up to n = 18. Luther and Mertens [9] set the current record by computing A 3 (19), improving and extending the original algorithm of Redelmeier [10] for counting polyominoes in the plane. To-date, no formula is known for A 3 (n) (or for the number of polycubes in any dimension).…”
Section: Introductionmentioning
confidence: 99%